"Bagatellen von - Beethoven?": Beethovens op. 119 und op. 126 zwischen Unterhaltung, Didaktik und Experiment - Rentsch, Ivana (Die Musikforschung, 2020)
Beethoven's contemporaries perceived the association of "the celebrated hero in music" with the trivial piano genre of the bagatelle as a paradox. Subsequent generations felt even more provoked by the chronological proximity of Beethoven's Bagatelles opp. 119 and 126 with the enigmatic late chamber music works. This article proproses a new and broader perspective on the Bagatelles beyond the "purely musical" by focusing on genre conventions (brevity and stylistic variety) as well as compositional context and intentions (pedagogy and the formation of good taste), against the background of their precarious aesthetic evaluation. This attention to context automatically highlights a practice which accounted for the majority of piano compositions published in the early decades of the nineteenth century, but which today can be reconstructed only rudimentarily.